The role of community health workers in the surgical cascade: a scoping review - Helen W. Li; Michael L. Scanlon; Nicholas Kisilu; Debra K. Litzelman (BMC, 2021)
Abstract Background Community health workers (CHWs) can increase access to various primary healthcare services; however, their potential for improving surgical care is under-explored. We sought to assess the role of CHWs in the surgical cascade, defined as disease screening, linkage to operative care, and post-operative care. Given the well-described literature on CHWs and screening, we focused on the latter two steps of the surgical cascade. Methods We conducted a scoping review of the peer-reviewed literature. We searched for studies published in any language from January 1, 2000 to May 1, 2020 using electronic literature databases including Pubmed/MEDLINE, Web of Science, SCOPUS, and Google Scholar. We included articles on CHW involvement in linkage to operative care and/or post-operative surgical care. Narrative and descriptive methods were used to analyze the data. Results The initial search identified 145 articles relevant to steps in the surgical cascade. Ten studies met our inclusion criteria and were included for review. In linkage to care, CHWs helped increase surgical enrollment, provide resources for vulnerable patients, and build trust in healthcare services. Post-operatively, CHWs acted as effective monitors for surgical-site infections and provided socially isolated patients with support and linkage to additional services. The complex and wide-ranging needs of surgical patients illustrated the need to view surgical care as a continuum rather than a singular operative event. Conclusion While the current literature is limited, CHWs were able to maneuver complex medical, cultural, and social barriers to surgical care by linking patients to counseling, education, and community resources, as well as post-operative infection prevention services. Future studies would benefit from more rigorous study designs and larger sample sizes to further elucidate the role CHWs can serve in the surgical cascade.